PREDICTORS OF ADVANCED LARYNGEAL SQUAMOUS CELL CARCINOMA INVASION ON THYROID GLAND TISSUE: Thyroid gland invasion in advanced laryngeal cancer - Radivojević, Nemanja S. (Medicinski podmladak, 2024)
Total laryngectomy presents the standard therapeutic protocol in the treatment of advanced laryngeal cancer. There is not enough research in this area to indicate the necessity of performing thyroidectomy in patients with advanced squamous cell carcinoma of the larynx, although some studies indicate that unilateral thyroidectomy is performed routinely in some centers. The National Comprehensive Cancer Network (NCCN) recommends ipsilateral hemithyroidectomy with laryngectomy for advanced squamous cell carcinoma of the larynx. However, in these cases, the risk of hypothyroidism and hypoparathyroidism is significantly higher, which requires postoperative monitoring of hormone status and thyroid replacement therapy. Invasion of the thyroid gland can occur due to direct or lymphovascular spread of advanced squamous cell carcinoma of the larynx, and the risk of locoregional recurrence and distant metastases in these cases increases significantly. The incidence of thyroid gland invasion in patients with advanced laryngeal squamous carcinoma is relatively low, and the most common predictors for infiltration are subglottic and transglottic extension of the laryngeal tumor, as well as direct invasion of the thyroid cartilage. Preservation of thyroid tissue during laryngectomy significantly reduces postoperative morbidity, however, thyroidectomy may be indicated if the presence of risk factors for thyroid invasion is assessed based on clinical, radiological and intraoperative findings. A careful assessment of risk factors is necessary to avoid the occurrence of locoregional recurrence, and thus a significantly worse prognosis.